Penggunaan Media Sosial Instagram @Adihidayat.Official sebagai Sumber Informasi Dakwah pada Pemuda Persis di Masa Pandemi Covid-19 - Abdulhamid Sofyan Harahap; Aning Sofyan (Bandung Conference Series: Communication Management, 2023)
Abstract. The development of social media, which continues to experience growth in Indonesia, is used by several parties to disseminate information, including Adi Hidayat. Instagram @Adihidayatofficial is a source of da'wah information for Persis youth, especially during the Covid-19 pandemic to meet their need for information. The method used in this research is a survey, this type of research includes correlational research. The population in this study were teenagers in the city of Bandung. The sample in this study were 98 respondents. The data analysis technique used is product moment correlation. The results of the study show the level of participation of Persis Youth members of the Batununggal Buah Batu Branch in the Instagram account @Adihidayat. Official makes it easy to connect followers and Instagram admins to each other. Overall the relationship between the two has been going well. Abstrak. Perkembangan media sosial yang terus mengalami perkembangan di Indonesia, dimanfaatkan oleh beberapa pihak untuk menyebarkan informasi termasuk oleh Adi Hidayat. Instagram @Adihidayatofficial menjadi sumber informasi dakwah bagi pemuda Persis terutama di masa pandemic Covid-19 untuk memenuhi kebutuhannya akan informasi. Metode yang digunakan dalam penelitian ini adalah survei, jenis penelitian ini termasuk penelitian korelasional. Populasi dalam penelitian ini adalah remaja di Kota Bandung. Sampel dalam penelitian ini adalah sebanyak 98 orang responden. Teknik analisis data yang digunakan adalah korelasi product moment. Hasil penelitian menunjukan Tingkat partisipasi anggota Pemuda Persis Cabang Batununggal Buah Batu di dalam akun instagram @Adihidayat. Official memudahkan untuk saling terhubungnya antara followers dengan admin Instagram. Secara keseluruhan keterhubungan antara keduanya sudah berjalan baik.